تدعيم الأعمدة البيتونية المسلّحة باستخدام الشبكات المعدنية الملحومة المتوافرة محلياً - كيخيا عبدالحميد; علي يامن (Latakia University Journal -Engineering Sciences Series, 2016)
يهدف هذا البحث إلى دراسة تدعيم الأعمدة البيتونية المسلحة الخاضعة لحمولة ضغط محورية باستخدام قمصان من الفيروسمنت (الملاط المسلح بشبك حديدي) Ferrocement والمحتوية على طبقتين من شبكات الأسلاك الملحومة Welded Wire Meshes المتوضعة ضمن طبقة من الملاط الإسمنتي العالي المقاومة. أجريت التجارب في مخبر البيتون ومواد البناء في كلية الهندسة المدنية بجامعة دمشق، وتمّ تحليل النتائج لمعرفة أثر طريقة التدعيم على كل من مقاومة الضغط القصوى للعمود ، مطاوعة العمود ، أشكال الانهيار. حيث بيّنت النتائج التجريبية فعالية استخدام شبكات الأسلاك الملحومة المتوافرة محلياً لتدعيم الأعمدة البيتونية المسلحة. This research paper revolves around studding the repairing of reinforced concrete columns which are subjected to an axial compression load, by using ferrocement jackets containing two layers of Welded Wire Meshes (WWMs), which are in turn encapsulated in high strength mortar. The experiments were carried out at the concrete lab in the faculty of civil engineering, Damascus University. The results were analyzed in order to determine the effects of repairing technique on Ultimate Compressive Strength, Ductility of the Column and Failure Modes. Empirical results confirmed the efficiency of using locally available welded wire meshes in repairing of reinforced concrete columns.